Structure and function of mitochondria in hepatopancreas cells from metabolically depressed snails. - Bishop, T; Ocloo, A; Brand, MD (2002)
Mitochondria in cells isolated from the hepatopancreas of aestivating land snails (Helix aspersa) consume oxygen at 30% of the active control rate. The aim of this study was to investigate whether the lower respiration rate is caused by a decrease in the density of mitochondria or by intrinsic changes in the mitochondria. Mitochondria occupied 2% of cellular volume, and the mitochondrial inner membrane surface density was 17 microm(-1), in cells from active snails. These values were not different in cells from aestivating snails. The mitochondrial protein and mitochondrial phospholipid contents of cells were also similar. There was little difference in the phospholipid fatty acyl composition of mitochondria isolated from metabolically depressed or active snails, except for arachidonic acid, which was 18% higher in mitochondria from aestivating snails. However, the activities of citrate synthase and cytochrome c oxidase in mitochondria isolated from aestivating snails were 68% and 63% of control, respectively. Thus the lower mitochondrial respiration rate in hepatopancreas cells from aestivating snails was not caused by differences in mitochondrial volume or surface density but was associated with intrinsic changes in the mitochondria.